2016
DOI: 10.1017/s0963548316000377
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Graphs of Prescribed Minimum Degree

Abstract: A graph $G$ is $H$-saturated if it contains no copy of $H$ as a subgraph but the addition of any new edge to $G$ creates a copy of $H$. In this paper we are interested in the function sat$_{t}(n,p)$, defined to be the minimum number of edges that a $K_{p}$-saturated graph on $n$ vertices can have if it has minimum degree at least $t$. We prove that sat$_{t}(n,p) = tn - O(1)$, where the limit is taken as $n$ tends to infinity. This confirms a conjecture of Bollob\'as when $p = 3$. We also present constructions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…For larger t and s, the bounds are not exact. In 2014, Day [6], resolving a conjecture of Bollobás [14] from 1996, showed that sat t (n, K s ) ≥ tn − c t (1) for any s ≥ 3, t ≥ s − 2. Here c t is a constant depending only on t. Further discussion on saturated graphs with degree constraints can be found in [10].…”
Section: History and Previous Resultsmentioning
confidence: 99%
“…For larger t and s, the bounds are not exact. In 2014, Day [6], resolving a conjecture of Bollobás [14] from 1996, showed that sat t (n, K s ) ≥ tn − c t (1) for any s ≥ 3, t ≥ s − 2. Here c t is a constant depending only on t. Further discussion on saturated graphs with degree constraints can be found in [10].…”
Section: History and Previous Resultsmentioning
confidence: 99%
“…Erdős, Hajnal and Moon [7] in 1964 initiated the study of the minimum number of edges over all K t -saturated graphs on n vertices (see the dynamic survey [8] on the extensive studies on K t -saturated graphs). Theorem 5 below is a result of Day [6] on K t -saturated graphs with prescribed minimum degree. It confirms a conjecture of Bollobás [1] when t = 3.…”
Section: Conjecture 3 (Hanson and Toftmentioning
confidence: 99%
“…We obtain a bad 2-coloring of G + y 2 v from c by coloring the edge y 2 v red, and then when t = 2, recoloring the edges yz 1 , z 1 y 1 , z 2 y 2 , y 2 z blue, the edges z 1 z, z 1 z 2 , and all the edges incident with y 2 in G b red; when t = 3, recoloring the edges y 1 z 1 , y 1 z 2 , zy 2 , zy 3 blue, the edges yy 1 , zz 1 , zz 2 , and all the edges between A and {y 2 , y 3 } in G b red. By (7), d b (y) = d b (z) = 2. By (5), yz / ∈ E(G).…”
Section: K 3 -Saturated Graphsmentioning
confidence: 99%